Co-encapsulated Ce6 + CpG and biopeptide-modified liposomes for enhanced transdermal photo-immunotherapy of superficial tumors - Shaozhen Wang; Chen Yang; Yuanyuan Zhang; Yi Hu; Lan Xiao; Weiping Ding; Bensheng Qiu; Fenfen Li (Materials Today Bio)
Cancer immunotherapy encounters challenges of a low treatment response rate due to the tumor immunosuppressive microenvironment and immune-related adverse events caused by off-target immunotherapy agents delivered through systemic administration in clinical practice. Photodynamic therapy (PDT) offers a viable approach to improve the immunotherapy efficacy through inducing immunogenic tumor cell death and is particularly advantageous in superficial tumor treatment. Therefore, leveraging integrated nanomaterials for photo-immunotherapy appears to be an ideal strategy to improve therapeutic outcome. In this study, we develop a transdermal-enhancing peptide (TD)-modified cationic liposome that simultaneously encapsulated with photosensitizer chlorine 6 (Ce6) and immunoadjuvant CpG, denoted as Ce6/CpG@Lip-TD, to mediate photo-immunotherapy of superficial tumors via the skin. The functionalization of TD peptide and positively charged surface endow the liposomes enhanced skin penetration capability. The combination of Ce6 and CpG within the liposomes synergistically potentiates the photo-immunotherapy effect when exposed to laser irradiation. In both melanoma and breast cancer murine models, Ce6/CpG@Lip-TD demonstrated substantial tumor-suppressing properties, along with an augmented systemic immune response against distal tumors. As a topical therapeutic agent, Ce6/CpG@Lip-TD circumvents the regulatory challenges associated with the systemic delivery of nanomaterials and significantly reduces systemic side effects, holding great promise for rapid translation into clinical applications.